On the Harmonic Evolute Surfaces of Hasimoto Surfaces - Eren, Kemal; Kelleci Akbay, Alev (Adiyaman University, 2021)
In this study, firstly by considering the evolution of a moving space curve, we give some related definitions and some new results about Hasimoto surfaces in Euclidean 3-spaces. Secondly, we examine harmonic evolute surfaces of Hasimoto surfaces in Euclidean 3-spaces and also, we give some geometric properties of these type surfaces. Moreover, we express the properties of parameter curves of harmonic evolute surfaces in Euclidean space. Finally, we give an explicit example of Hasimoto surface and its harmonic evolute surface and also we plot these surfaces. © 2021, Adiyaman University. All rights reserved.
Hasimoto Yüzeylerin Harmonik Evrim Yüzeyleri Üzerine
Keywords: Binormal motion; Evolution of curves and surfaces; Gaussian curvature; Harmonic evolute surface; Hasimoto surfaces; Mean curvature